(untitled) (Conferencea, 2023)
The article reveals the syntax of a complex sentence in modern Russian and the syntactic structure, the main grammatical features, the difference from a simple sentence, as well as the connection between its parts. The information about a complex sentence from the scientific research of the authors of well–known books on this topic is given, that it has its own classification, since the classification of complex sentences is a classification according to the syntactic connection between its parts. The author gives examples of a complex sentence from many literatures, they are the basis for studying a scientific article.